Impact of total contact plaster boot via off loading practice in trophic ulcers of the feet: case series. - Sundaresan AN; Vikram M; Mohandas K; Nur Farhana MY; Potturi Gowri S; Mahendran J (Penerbit UKM, 2014)
Trophic ulcers have emerged as one of the major complications following diabetes mellitus (DM) and Hansen’s diseases (HD). In this case series, the study attempted total contact plaster boot using a readily available plaster of Paris to treat trophic ulcer for 10 subjects. A total of five subjects with DM and five subjects with HD were included based on the study criteria. Pre and post test measure of wound measurement size following total contact plaster boot were taken as an outcome measure. All ten subjects showed decrease in size of wound following fifteen days of treatment. No adverse effects were associated with this type of treatment. Subjects with trophic ulcer may benefit from the application of total contact plaster boot.